PEMODELAN ZONA SESAR OPAK DI DAERAH PLERET BANTUL YOGYAKARTA DENGAN METODE GRAVITASI - Nurwidyanto, M. Irham; Dwi Indriana, Rina; Thaha Darwis, Zukhrufuddin (BERKALA FISIKA, 2007)
A gravity research was done in Pleret, Bantul, Yogyakart.It’s covering 55 measurements points. This research aims to estimated subsurface structure  fault zone of the area, correctly along Opak River’s. Type of Gravitymeter La Coste & Romberg G-1118 using electronics feedback system with accuracy 0.005 miligal was used to measure gravitational field. Interpretation result from kualitative and kuantitative  are  estimated the structure in the research area consist of tree layer that arre  limestone, breccia, and alluvial sediment and Opak sediment’s